Diminazene Aceturate (DIZE) Ameliorates Hypertension and Induces Anxiolytic- and Antidepressant-like Effects in TGR(mRen2)27 - Costa, Laura Amado; Mourão, Flávio A.G.; Alenina, Natalia; Bader, Michael; Campagnole-Santos, Maria José; Kangussu, Lucas M. (Protein and Peptide Letters, 2025)
IntroductionDiminazene aceturate (DIZE) was described as an angiotensin-converting enzyme 2 (ACE2) activator. ACE2/Angiotensin-(1-7)/Mas receptor axis presents protective actions on cardiovascular diseases and plays an important modulatory role in the neurobiology of mood and anxiety disorders.ObjectivesTo evaluate the effects of chronic intracerebroventricular (ICV) treatment with DIZE on blood pressure, anxiety- and depression-like behaviors in hypertensive transgenic (mRen2)27 rats (TGR).MethodsMale TGR and Sprague-Dawley rats (10-12 weeks old) were subjected to chronic ICV infusion of DIZE (1.0 µg/h for 7 days). Blood pressure and heart rate were measured by tail plethysmography and anxiety- and depression-like behaviors were evaluated through elevated plus maze, marble burying and forced swim tests, respectively.ResultsTreatment with DIZE induced a significant reduction in mean arterial pressure in both TGR and SD rats. A decrease in heart rate was only observed in the hypertensive animals. Additionally, treatment with DIZE attenuated the anxiety- and depression-like behaviors that were observed in TGR.ConclusionDIZE has central anti-hypertensive, anxiolytic, and anti-depressive effects.
Keywords: depression